Influence of growth regulators on the vegetative propagation of lavender (Lavandula angustifolia) - Quito León, Erik Patricio; Escalante Gavilanes, Carlos Alberto; Muñoz López, Carmen Emelia; Guillen Palma, Tanya Paola; Valarezo Quinaluisa, Rodrigo Andrés (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2024)
The research was carried out in the Guayaquil canton, Guayas province, with the aim of investigating alternatives for asexual reproduction using growth regulators in lavender stem cuttings. Three growth regulators were studied: 1-Naphthaleneacetic acid (ANA) (Hormonagro), Stimplex biostimulant (based on the seaweed Ascophyllum nodosum) diluted in water; and Aloe barbadensis mucilage directly on the cuttings, and distilled water as a control. A completely randomized design was used with four treatments and four replications, measuring five variables after 45 days. It was concluded that the T4 treatment, aloe (Aloe barbadensis), showed better results in terms of number of roots, number of leaves and number of buds, suggesting that this organic product may be favorable for the reproduction of lavender plants by means of cuttings. That with the three growth regulators all the variables evaluated increase, although no significant statistical differences were found, only numerical differences between the growth regulator treatments, regarding the variables number of roots, survival percentage and cutting height.
Keywords: Lavender; growth regulators; aloe